BASCOM-AVR DAN KOMPONEN ATMEGA8535 DIIMPLEMENTASIKAN PADA PERANGKAT PENANGKAP IKAN - Armansyah, Armansyah (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2018)
For fishermen, fishing traditionally is a job that takes a long time. The existence of a point where a bunch of fish gather is also difficult to determine if traditional methods are taught which sometimes get an estimate that often misses. This study aims to design a device that serves to catch fish automatically and apply the detection of the presence of fish in a shallow water. By using Atmega8535 microcontroller component, and BASCOM-AVR, fishing can be done easily because it implements tool automation on fish network. Keywords: Algorithm, Fish Catcher, Microcontroller, Atmega8535, BASCOM-AVR